NETRALITAS PEGAWAI NEGERI SIPIL DALAM PEMILIHAN KEPALA DAERAH - Mat Zudi, Arief Hidayat, Untung Sri Hardjanto (Diponegoro Law Journal, 2012)
The neutral of civil servant actually is bureaucracy in which still remain the same at public services, even the goverment changes. It is because of public services will not change even the goverment staffs change. It means that all staffs in goverment always service the public based on professionalism and not only because of political will. The position of civil servants still can be honoured and they have right to vote on goverment for district election. In this case, the civil servants placed on strategics part as all candidates of goverment staff as them votesgetters. All candidates are sure that every civil servant can be as votesgetters for 5 to 10 or more voters in district election.